Bleeding in Hepatic Surgery: Sorting through Methods to Prevent It. (18th November 2012) - Romano, Fabrizio; Garancini, Mattia; Uggeri, Fabio; Degrate, Luca; Nespoli, Luca; Gianotti, Luca; Nespoli, Angelo; Uggeri, Franco
Abstract : Liver resections are demanding operations which can have life threatening complications although they are performed by experienced liver surgeons. The parameter "Blood Loss" has a central role in liver surgery, and different strategies to minimize it are a key to improve results. Moreover, recently, new technologies are applied in the field of liver surgery, having one goal: safer and easier liver operations. The aim of this paper is to review the different principal solutions to the problem of blood loss in hepatic surgery, focusing on technical aspects of new devices.